2008
DOI: 10.1007/s10482-008-9249-8
|View full text |Cite
|
Sign up to set email alerts
|

recA mediated spontaneous deletions of the icaADBC operon of clinical Staphylococcus epidermidis isolates: a new mechanism of phenotypic variations

Abstract: Phenotypic variation of Staphylococcus epidermidis involving the slime related ica operon results in heterogeneity in surface characteristics of individual bacteria in axenic cultures. Five clinical S. epidermidis isolates demonstrated phenotypic variation, i.e. both black and red colonies on Congo Red agar. Black colonies displayed bi-modal electrophoretic mobility distributions at pH 2, but such phenotypic variation was absent in red colonies of the same strain as well as in control strains without phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 25 publications
1
28
1
Order By: Relevance
“…Furthermore, Nuryastuti et al (35) showed that deletion of the ica operon from S. epidermidis can be caused by the deregulation of RecA, which is involved in genetic deletions and rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Nuryastuti et al (35) showed that deletion of the ica operon from S. epidermidis can be caused by the deregulation of RecA, which is involved in genetic deletions and rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical isolates of S. epidermidis were screened for the presence of icaA by PCR using the primers listed in Table 2 (19,32,40). Briefly, S. epidermidis strains were grown overnight at 37°C on a TSB agar plate.…”
Section: Bacterial Strains Sixteen Clinical Isolates Of S Epidermidismentioning
confidence: 99%
“…Biofilm formation in the presence of cinnamon oil and the effect on icaA expression. Biofilms were grown as described previously (7,32). Briefly, wells of a 96-well tissue culture polystyrene microtiter plate (Falcon; Becton Dickinson Labware, Franklin Lakes, NJ) were filled with 100 l of TSB containing cinnamon oil (twofold final concentrations) and subsequently inoculated with a 1:100 dilution of an overnight culture.…”
Section: Vol 75 2009 Effect Of Cinnamon Oil Against S Epidermidis mentioning
confidence: 99%
See 2 more Smart Citations